Coefficients of the weighting optimal quadrature formula in the Sobolev space (Международный научный журнал «Инженер», 2026)
In this paper, an optimal quadrature with weight in the Sobolev space is constructed for . The optimalcoefficients of the constructed weight quadrature formula were found in the form of an analytical formulausing the Sobolev method.